Headache in children: update on complementary treatments - Schetzek, Stefanie; Heinen, Florian; Kruse, Sigrid; Borggraefe, Ingo; Bonfert, Michaela; Gaul, Charly; Gottschling, Sven; Ebinger, Friedrich (Neuropediatrics, 2013)
Complementary and alternative medicine (CAM) is widely used by both physicians and patients with primary headache syndromes. Despite a considerable number of articles addressing CAM in primary headache syndromes, the overall evidence for CAM is still poor. The aim of this review was to give an overview of the current evidence of the main alternative therapies used in the treatment of primary headache syndromes of childhood. MEDLINE and Cochrane Library were systematically searched for articles dealing with complementary and alternative treatment or prophylaxis of headache and migraine published within the past 20 years.